In vitro angiotensin-converting enzyme (ACE) inhibition activity of Syzygium polyanthum leaves and its inhibition mechanism - Ismail, Azlini; Tuan Anuar, Tuan Ashraf Faiz; Mohamed Suffian, Izzat Fahimuddin; Abdul Hamid, Azzmer Azzar; Omar, Muhammad Nor (Frontiers, 2021)
Syzygium polyanthum is an ethnomedicinal plant with significant antihypertensive effect; however, the mechanism of action is not yet well-described. This study aims to investigate one of its possible antihypertensive mechanisms, the angiotensin-converting enzyme (ACE) inhibition and its inhibition mechanism. S. polyanthum leaves were macerated using water, methanol, ethyl acetate, and hexane to produce the aqueous (ASP), methanolic (MSP), ethyl acetate (EASP) and hexane (HSP) extracts. Each extract (100 μg/ml) was screened for in vitro ACE inhibition activity according to Cushman and Cheung assay method. The standard drug, captopril (2.06 ng/ml) was used as a positive control. The most active extract was further tested at 1 to 1000 μg/ml to determine its potency. A similar assay was then conducted in the presence of zinc chloride or bovine serum albumin (BSA) to determine ASP’s ACE inhibition mechanism. ASP was found to exhibit the highest inhibition activity (69.43 ± 0.60 %), followed by HSP (45.40 ± 0.15 %), MSP (41.63 ± 0.15 %), and EASP (9.62 ± 1.60 %). The concentration of ASP that caused 50 % ACE inhibition activity (IC50) was 41 μg/ml. ASP’s ACE inhibition activity was significantly reduced with the presence of BSA but not significantly affected by the presence of zinc chloride. In conclusion, S. polyanthum leaves possessed a significant ACE inhibition activity which was majorly present in its aqueous extract. It is postulated that ASP’s ACE inhibition activity was due to its ability to conjugate with protein, and it was non-dependent on the zinc at the ACE active site.